Inverse Association Between Circulating Monocyte-Platelet Complexes and Inflammation in Ulcerative Colitis Patients. Issue 4 (23rd February 2018) - Zamora, Carlos; Canto, Elisabet; Nieto, Juan C; Garcia-Planella, Ester; Gordillo, Jordi; Ortiz, Mª Angels; Suarez-Calvet, Xavier; Perea, Lidia; Julia, Germà; Juarez, Candido; Vidal, Silvia
Abstract: Background: Circulating monocytes from active ulcerative colitis (UC) patients produced high levels of tumor necrosis factor-alpha(TNFα) and interleukin(IL)-6 after Toll-like receptors (TLR) stimulation. Since platelets (PLT) can bind to leukocytes, thereby decreasing inflammatory cytokine production, UC patients may exhibit different levels of monocyte-platelet complexes depending on disease activity. Methods: We compared among healthy donors, active (onset flare and relapse), and inactive UC patients the presence of circulating monocyte-platelet complexes (CD14+PLT+) and membrane CD162 expression by flow cytometry. Lipopolysaccharide- binding protein, TNFα, and IL-10 were compared by ELISA. Binding of CD14+PLT+ to human umbilical vein endothelial cells (HUVECs) were analyzed by immunofluorescence. Results: Onset flare UC patients had the lowest levels of CD14+PLT+. Membrane CD162, crucial for the PLT binding, was downregulated only on monocytes from onset flare UC patients. Membrane CD162 expression on CD14+ cells inversely correlated with lipopolysaccharide binding protein levels. As an expected consequence, more CD14+PLT+ than CD14+PLT- from onset flare UC patients bound to activated HUVECs. TNFα tended to negatively correlate with CD14+PLT+ in relapse and inactive UC patients, whereas IL-10 positively correlated with CD14+PLT+ in all UC patients (r = -0.43, P = 0.1 and r = 0.61, P = 0.01, respectively). The anti-inflammatory role of PLT binding to monocytes was confirmed in cocultures of PLT and monocytes. These cocultures increased the percentage of CD14+PLT+ and IL-10 production, and decreased TNFα production. These anti-inflammatory effects were abolished when we blocked the binding of PLT with neutralizing anti-CD62P antibody. Conclusions: Decreased CD162 expression associated with endotoxemia reduced the binding of PLT to monocytes through membrane CD162-CD62P, favoring the inflammatory response of onset flare UC patients.